Blood-Biomarkers for Glucose Metabolism in Preterm Infants - Mia O. Bjerager; Bo M. Hansen; Frederik Sørensen; Jes R. Petersen; Kristian V. Jensen; Brian R. Hjelvang; Anna C. Hvelplund; Dorte A. Olsen; Aneta A. Nielsen; Julie L. Forman; Ivan Brandslund; Gorm Greisen; et al. (Biomedicines, 2023)
This was an exploratory, prospective, longitudinal, cohort study that aimed to establish “healthy” reference levels related to growth parameters and glucose metabolites in preterm infants. This was conducted to further investigate growth and metabolic disturbances potentially related to neonatal illness. The study sample consisted of 108 preterm infants born before 32 weeks in 2018–2019 in the Capital Region of Denmark. Repetitive blood samples were acquired at the neonatal wards, while clinical data were obtained from the regional hospital medical record system. Thirty-four “healthy” preterm infants (31%) were identified. The “ill” infants were divided into four subgroups dependent on gestational age and small for gestational age. Reference levels for the growth parameters and metabolic biomarkers glucose, albumin, and adiponectin, and two glucose control indicators, glycated albumin and fructosamine, were determined for the “healthy” and “ill” subgroups. The “ill” extremely preterm infants had increased glucose levels (mean difference 0.71 mmol/L, 95% CI 0.23; 1.18 mmol/L) and glycated albumin (corrected; %) (mean difference 0.92 mmol/L, 95% CI 0.38 mmol/L;1.47 mmol/L) compared to the “healthy” infants. In “ill” extremely preterm infants and “ill” very preterm infants born small for gestational age, levels of biomarkers containing proteins were decreased. In the “Ill” extremely preterm infants and infants born small for gestational age, postnatal growth was continuously decreased throughout the postconceptional period. The short-term glucose-control indicator, glycated albumin (corrected; %), reflected well the high glucose levels due to its correction for the depleted plasma-protein pool.